Draft Ninth Five Year Plan (1997-2002) Andhra Pradesh Volume II (Sectoral Programmes) Energy - Planning Commission (Planning Commission, 1997)
Energy is essential input for economic development and for improving the quality of human life. the growth in the economy has been fuelled by exploitation of commercial fuel resources. the extension of Electricity Supply to large number of habitation has resulted in improvement in the quality of life in general.
Finance and Planning (Plg. Wing) Department, Government of Andhra Pradesh